Analisis Instrumentasi Pada Pengendali Lampu Otomatis Bluelight Control Berbasis Arduino Uno - Arianto, Calvin; Nurpulaela, Lela; Hidayat, Rahmat (Peneliti.net, 2024)
In tandem with the contemporary temporal progression, technology has undergone rapid advances, with electronics emerging as pivotal agents in the evolution of domiciliary comfort systems. Ambient illumination pervades as a fundamental facet of quotidian human existence. Presently, the administration of luminal states predominantly adheres to manual toggles, a methodology that bespeaks inefficacy, given its entreaty for human intervention. In acknowledgment of the constraints of manual toggles, a lacuna emerges for an innovative panacea manifesting as an autonomous luminosity modulation system, enacting either automated luminosity control or facilitating telesthetic governance. Consequentially, the instantiation materializes as an automated luminosity modulator. This modulator is subjugated into an amalgamation of pivotal constituents, encompassing the smartphone, Arduino UNO microcontroller, relay module, and HC-05 Bluetooth module. Emanating luminosity entails the smartphone's issuance of directives to the Arduino, by virtue of the HC-05 Bluetooth interlinkage, thereby activating the relay module—effectuating its role as a switch—to regulate luminous intensity congruent with the smartphone's mandates. This orchestration augments not only the optimization of domestic luminosity administration but also a noteworthy curtailment of human agency necessitated in the orchestration of this quotidian enterprise. The efficacious instantiation of the automated luminosity modulator harbors propitious prospects for an efficacious trifecta: energy efficiency, hedonic amplification, and quotidien convenience. By obviating dependence on manual toggles and conferring judicious control, the technology has the capacity to mitigate unwarranted energy dissipation resultant from idle luminosity states. Moreover, user satisfaction is engendered by circumventing the need to locate physical toggles, obviated by the omnipresence of the smartphone. The utility of the HC-05 Bluetooth module in this instantiation confers long-distance luminosity manipulation, an asset acutely advantageous in circumstances mandating remote luminosity control, notably instances entailing illumination manipulation pre-entry or post-egress. Ergo, this system augments not only quotidian convenience but also the malleability requisite for bespoke luminosity administration. In summation, the automated luminosity modulator epitomizes affirmative technological strides catalyzing enhanced domestic comfort and efficiency. By streamlining luminosity administration and attenuating human involvement therein, this technological innovation forges a trajectory toward an enlightened and eco-friendly lifestyle paradigm.